DEMQOL and DEMQOL-Proxy: a Rasch analysis among those diagnosed with dementia - A. A. Jolijn Hendriks; Sarah C. Smith; Nick Black (Health and Quality of Life Outcomes, 2019)
Abstract Background In previous work we concluded that DEMQOL and DEMQOL-Proxy can provide robust measurement of HRQL in dementia when scores are derived from analysis using the Rasch model. As the study sample included people with mild cognitive impairment, we undertook a replication study in the subsample with a diagnosis of dementia (PWD). PWD constitute the population for whom DEMQOL and DEMQOL-Proxy were originally developed. Methods We conducted a Rasch model analysis using the RUMM2030 software to re-evaluate DEMQOL (441 PWD) and DEMQOL-Proxy (342 family carers). We evaluated scale to sample targeting, ordering of item thresholds, item fit to the model, and differential item functioning (sex, age, severity, relationship), local independence, unidimensionality and reliability. Results For both DEMQOL and DEMQOL-Proxy, results were highly similar to the results in the original sample. We found the same problems with content and response options. Conclusions DEMQOL and DEMQOL-Proxy can provide robust measurement of HRQL in people with a diagnosis of dementia when scores are derived from analysis using the Rasch model. As in the wider sample, the problems identified with content and response options require qualitative investigation in order to improve the scoring of DEMQOL and DEMQOL-Proxy.